COMPARISON OF MODEl PREDICTIONS AND SPEED TRIAL RESULTS fOR A GROUP Of 32' WOODEN TRAWLERS - RAJENDRAN, R; SAIN, V (Fishery Technology, 2025)
Speed trial results of six 32' wooden sternÂ· trawlers built to thesame design are analysed to determine the EHP ship-- Froude numbercurves in each case .and are compared with the model test results ofthe same design and for the corresponding displacement ~conditions